Nowe filmy biblijne – między ortodoksją a apokryfem = New Biblical Films – Between Orthodoxy and Apocrypha - Lis, Marek (Studia religiologica, 2016)
Although biblical movies could be considered an almost defunct genre, television and cinema audiences in the first years of the 21st century are discovering a new interest of producers, motivated more by the desire for profit than by religious reasons. Among films, modern audiovisual apocrypha, we can observe new tendencies: animated feature films aimed at large family audiences, the appearance of a “professional Jesus” (Bruce Marchiano), and the tendency to put the figure of historical Jesus in modern ahistorical situations and in racial contexts (black Jesus).